2021
DOI: 10.1007/s12649-021-01415-z
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technology for Processing Urban Waste Compost as a Fast-Releasing Nitrogen Source to Improve Soil Properties and Broccoli and Lettuce Production

Abstract: Purpose: This study evaluated nitrogen (N) mineralization dynamics in three soils after the addition of heattreated urban waste amendments or urban waste compost (UWC). The effects of UWC and urea on soil properties and broccoli and lettuce production were compared. Methods: The rst N mineralization experiment was conducted in a factorial arrangement (4 × 3), as a randomized complete block design (RCBD), with three replicates. Four UWC doses: 12.5, 25.0, 37.5, and 50.0 mg dm -3 were applied to three soils: san… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The data of the variables described above were submitted to the assumptions of normality and homogeneity of variance by the Shapiro-Wilk and Levenne tests, respectively. A Person's correlation analysis, to verify the relationship between Si and Al concentrations were submitted 59 . Additionality, a multivariate analysis (two-way ANOVA) with Al and Si factors, as well as their interactions (Al × Si) were submitted.…”
Section: Discussionmentioning
confidence: 99%
“…The data of the variables described above were submitted to the assumptions of normality and homogeneity of variance by the Shapiro-Wilk and Levenne tests, respectively. A Person's correlation analysis, to verify the relationship between Si and Al concentrations were submitted 59 . Additionality, a multivariate analysis (two-way ANOVA) with Al and Si factors, as well as their interactions (Al × Si) were submitted.…”
Section: Discussionmentioning
confidence: 99%
“…The data of the variables described above were submitted to the assumptions of normality and homogeneity of variance by the Shapiro–Wilk and Levenne tests, respectively. A Person’s correlation analysis, to verify the relationship between Si and Al concentrations were submitted 62 . Additionality, a multivariate analysis (two-way ANOVA) with Al and Si factors, as well as their interactions (Al × Si) were submitted.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from AMF and PGPR, the organic production of lettuce has relied on the application of organic materials, such as manures, humus-rich composts, and seaweed extracts (in foliar applications), in order to boost plant growth and yield, increase nutrient uptake and mycorrhizal colonization, and improve the antioxidant responses of L. sativa [23][24][25]. In addition, urban waste compost application improved soil properties and increased lettuce production [26]. In another comparative study, organic amendments applied to lettuce and orchardgrass were shown to supply adequate levels of N while resulting in good productivity [27].…”
Section: Introductionmentioning
confidence: 99%